Antimicrobial Activity of Oleanolic and Ursolic Acids: An Update - Jesus, Jéssica A. (Evid Based Complement Alternat Med, 2015)
Triterpenoids are the most representative group of phytochemicals, as they comprise more than 20,000 recognized molecules. These compounds are biosynthesized in plants via squalene cyclization, a C(30) hydrocarbon that is considered to be the precursor of all steroids. Due to their low hydrophilicity, triterpenes were considered to be inactive for a long period of time; however, evidence regarding their wide range of pharmacological activities is emerging, and elegant studies have highlighted these activities. Several triterpenic skeletons have been described, including some that have presented with pentacyclic features, such as oleanolic and ursolic acids. These compounds have displayed incontestable biological activity, such as antibacterial, antiviral, and antiprotozoal effects, which were not included in a single review until now. Thus, the present review investigates the potential use of these triterpenes against human pathogens, including their mechanisms of action, via in vivo studies, and the future perspectives about the use of compounds for human or even animal health are also discussed.